2007
DOI: 10.1590/s1807-59322007000200011
|View full text |Cite
|
Sign up to set email alerts
|

Williams Syndrome. Development of a New Scoring System for Clinical Diagnosis

Abstract: OBJECTIVE:To develop a scoring system based on clinical findings to assist pediatricians in the diagnosis of William syndrome and to delineate when the fluorescent in-situ hybridization test to detect the microdeletion at 7q11.23 may be needed. METHODS:The fluorescent in-situ hybridization test was performed on 20 patients presenting William syndrome suggestive clinical features. Eleven studies were selected from the literature in which there were 2 groups: patients with positive or negative fluorescent in-sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
(20 reference statements)
0
13
0
2
Order By: Relevance
“…These findings underscore the importance of experienced clinical and psychological assessments in cases where a specific diagnosis is suspected, but the presentation is atypical. Obviously this is not always possible, but the development of syndrome-specific matrices for facial features [Hammond et al, 2005], growth parameters [Martin et al, 2007] cognitive or behavioral profiles [Mervis and Klein-Tasman, 2000] or for overall clinical presentation [Sugayama et al, 2007] should help with accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings underscore the importance of experienced clinical and psychological assessments in cases where a specific diagnosis is suspected, but the presentation is atypical. Obviously this is not always possible, but the development of syndrome-specific matrices for facial features [Hammond et al, 2005], growth parameters [Martin et al, 2007] cognitive or behavioral profiles [Mervis and Klein-Tasman, 2000] or for overall clinical presentation [Sugayama et al, 2007] should help with accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the clinical diagnostic scoring systems proposed by Lowery et al (1995), AAP (2001), and Sugayama et al (2007) were used in 250 patients with WBS: 149 Brazilian patients [140 FISH (+) and 9 FISH (-)], and 101 patients from Argentina [88 FISH (+) and 13 FISH (-)]. Lowery et al (1995) reviewed the clinical findings for 110 patients with WBS confirmed by FISH, and developed a scoring system that classified WBS patients according to 6 different phenotypes.…”
Section: Methodsmentioning
confidence: 99%
“…The scoring system of Sugayama et al (2007) is based on a meta-analysis including 577 patients and 42 clinical signs. The cut-off score indicating the need for the FISH test is 20.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations